Pengaruh Perceived Ease Of Use, Perceived Usefulness Dan Perceived Security Terhadap Customer Satisfaction Pengguna E-Wallet Dana Pada Mahasiswa Feb Universitas Islam Malang Angkatan 2020-2023 - Syah, Putra Andreyan; Rachma, N.; Athia, Ita (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The research objectives to be achieved, this type of research is explanatory research using a quantitative approach. In this research, the population is students from the Faculty of Economics and Business, Islamic University of Malang, Class of 2020-2023 who use the Dana application. Because the population size is not known with certainty, the sample size used was according to Malhotra's opinion by multiplying the number of indicators used in the research by 5 and a total of 80 respondents were found. The research uses multiple linear regression analysis using the SPSS 25 application. The research results show that perceived ease of use, perceived usefulness and perceived security have a simultaneous and partial effect on customer satisfaction. Keywords: Perceived ease of use, Perceived usefulness, Perceived security and Customer satisfaction